Analysis of the Influence of High-Dose rhGH Therapy on Serum Vitamin D and IGF-1 Levels in School-Age Children with Idiopathic Short Stature. (26th October 2021) - Li, Juan; Zhang, Xuehui; Xie, Shuyong; Feng, Shuangshuang; Niu, Min
Abstract : Objective . To discuss the influence of high-dose recombinant human growth hormone (rhGH) therapy on serum vitamin D and insulin-like growth factor-1 (IGF-1) levels in school-age children with idiopathic short stature (ISS). Method . A total of 103 school-age children with ISS were selected from June 2016 to June 2020 in our hospital. The enrolled cases were divided into the low-dose group ( n  = 59) and high-dose group ( n  = 44) according to the treatment dose of rhGH. After the treatment, the height (Ht), height standard deviation score (Ht SDS), growth velocity (GV), and other indicators were recorded. The serum 25-hydroxy vitamin D [25-(OH)D] and IGF-1 levels of the two groups were tested, and the occurrence of adverse reactions was recorded. Results . After treatment, the high-dose group outperformed the low-dose group in various growth effect indicators such as Ht, Ht SDS, and GV (P < 0.05 ). After treatment, the serum 25-(OH)D of children with ISS in the two groups increased significantly, but there was no significant difference between the two groups (P > 0.05 ). After treatment, the serum IGF-1 of children with ISS in the two groups increased significantly, but there was no significant difference between the two groups (P > 0.05 ). For children with ISS, adverse reactions induced by rhGH therapy were very rare. There was no significant difference in the incidence of adverse reactions induced by different doses of rhGH in the treatment of ISS (P > 0.05 ). Conclusion . rhGH has definite efficacy in the treatment of ISS children, for it can significantly increase the annual growth rate of ISS children in a dose-dependent manner. High-dose rhGH for ISS has a better therapeutic effect. At the same time, regardless of the dose level of rhGH, serum 25-(OH)D and IGF-1 levels in children with ISS were increased, with less adverse reactions and higher safety.